2002
DOI: 10.1002/app.11539
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of calcium silicate‐filled isotactic polypropylene

Abstract: ABSTRACT:The melt rheological behavior of calcium silicate-filled isotactic polypropylene, with filler volume contents of 0 -17.8%, was determined at 493 K. The composites followed the power law in shear stress versus shear rate variations and were shear thinning. Initially, apparent melt viscosity decreased until a critical filler volume content of 8.5% was reached. However, on further increase in calcium silicate concentration, apparent melt viscosity increased. Melt elasticity also showed an initial decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
17
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 20 publications
7
17
1
Order By: Relevance
“…In i-PP=Al 2 O 3 composites at low f F values a flow favoring orientation of acicular Al 2 O 3 particles may give rise to this lowering of shear stress (4). Similar results were observed in iPP=Kaolin composites as well (11). In the i-PP=Al 2 O 3 =LICA 38 systems the flow curves also exhibit similar characteristics as their counterparts; at a fixed shear rate the extent of decrease and subsequent increase of shear stress is, however, less due to the modifying effect of LICA 38 through bonding of i-PP with Al 2 O 3 .…”
Section: Shear Stress-shear Rate Curvessupporting
confidence: 84%
See 3 more Smart Citations
“…In i-PP=Al 2 O 3 composites at low f F values a flow favoring orientation of acicular Al 2 O 3 particles may give rise to this lowering of shear stress (4). Similar results were observed in iPP=Kaolin composites as well (11). In the i-PP=Al 2 O 3 =LICA 38 systems the flow curves also exhibit similar characteristics as their counterparts; at a fixed shear rate the extent of decrease and subsequent increase of shear stress is, however, less due to the modifying effect of LICA 38 through bonding of i-PP with Al 2 O 3 .…”
Section: Shear Stress-shear Rate Curvessupporting
confidence: 84%
“…At a constant-g w , the Z app at first-decreases up to alumina volume % f F ¼ 5.8 whereas beyond this f F the data increased with f F . Similar results were observed in i-PP composites with kaolin and CaSiO 3 [11,12].…”
Section: Apparent Melt Viscosity (Z App )supporting
confidence: 76%
See 2 more Smart Citations
“…It has, therefore, received extensive attention in the past two decades. [15][16][17][18] In a study on rheological properties of calcium silicate-filled isotactic PP, Maiti et al 19 found that the apparent melt viscosity of the composites decreased until a critical filler volume content of 8.5% was reached. However, with further increase in calcium silicate concentration, apparent melt viscosity increased.…”
Section: Introductionmentioning
confidence: 99%